What do primary care doctors do when they fall sick? A qualitative study exploring their help-seeking behavior - Ng, C.J.; Nik-Sherina, H. (2005)
Aim: To explore the help-seeking behavior of primary care doctors during illness. Methods: This qualitative study used focus group discussions to explore participantsâ help-seeking behavior during illness. It involved 22 primary care doctors (5 lecturers, 12 postgraduate trainees, 5 medical officers) working in a hospital-based primary care clinic. Result: Most primary care doctors in this study managed their illnesses without seeking help. Although most preferred to seek professional help for chronic illnesses and antenatal care, they tend to delay the consultations and were less likely to comply with treatment and follow-up. Explanations for their behavior include their ability to assess and treat themselves, difficulty to find suitable doctors, work commitment, easy access to drugs, and reluctance to assume a sick role. Conclusions: This study found that the help-seeking behavior of primary care doctors was similar to those in other studies. Due to their professional ability, heavy workload and expectations from peer and patients, primary care doctors were more likely to delay in seeking treatment especially for chronic and serious diseases. This highlights the need to enhance support services for doctors during illness.